Evaluating the chloride permeability of steel–concrete interface based on concretes of different stability. (25th August 2020) - Cai, Yuxin; Zhang, Wulong; Yang, Changhui; François, Raoul; Yu, Linwen; Chen, Mengzhu; Chen, Hang; Yang, Huan
Abstract: The deterioration of reinforced concrete structures caused by chloride‐induced corrosion is a major threat to their service life. Previous studies show that defects in the steel–concrete interface have a significant impact on the corrosion process of steel bars. Study on the chloride permeability of steel–concrete interface is very important for revealing the mechanism. In this article, we devised a new experimental method named chloride penetration depth test which was used to evaluate the chloride permeability along the steel–concrete interface. Two types of fresh concretes, normal concrete (NC) and lightweight aggregate concrete (LWAC) with obviously different stability, were designed to obtain specimens of various defect sizes in the steel–concrete interface. The results show that the chloride penetration depth measured with the new method increased with the defect size in the steel–concrete interface determined by backscattered electron (BSE) imaging and nanoindentation technology, indicating that the chloride permeability of steel–concrete interface could be identified by the method we proposed.